SISTEM PENDUKUNG KEPUTUSAN KELOMPOK UNTUK PEMILIHAN TANAMAN PERTANIAN LAHAN KERING - , DWINY MEIDELFI; , Dra. Sri Hartati, M.Sc., Ph.D, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Dryland agricultural is a land used for planting crops using limited water supply, but sometimes, it only relies on rainfall. However, the number of agricultural lands are decreasing. The Department of Agriculture is Indonesian department responsible for giving counseling service in order to increase and optimize this sector. The import dependency is expected to be reduced by increasing the farmerâs productivity. In addition, the cropping patterns, marketing, and production quality are some indicators that support productivity. This research discusses about a group decision support system to select dryland crops using nearest neighbor and borda. Nearest neighbor is used to determine the priority crops and land. The priority has been set by the decision makers, while borda is used to merge the decision makerestimation. This system will generate the rank of crops priority, which help the decision maker to get the best decision.